IMPLEMENTASI METODE LEARNING START WITH A QUESTION PADA PEMBELAJARAN AKIDAH AKHLAK - Latifatul Fauzia (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
This research study aims to determine the implementation of the learning start with a question method in learning akidah morals at MA Mazro'atul Huda Wonorenggo Karanganyar Demak, as well as the supporting and inhibiting factors in this implementation. Qualitative method is a method used in this research, namely an approach that aims to understand a phenomenon in depth. The subjects of this research were the head of Madrasah, a teacher of akidah akhlak at MA Mazro'atul HudaWonorenggo Karanganyar Demak and one female student of class X IPA 1. Data about the implementation of the learning method start with a question on learning akidah akhlak at MA Mazro'atul. Huda Wonorenggo Karanganyar Demak was collected by interviewing, observing, and using documentation study. After the researcher went directly to the field and collected data accurately and analyzed it, the results showed that: First, the learning method start with a question is an innovative method in learning that can create situations and conditions for students to be much more active in learning and can develop the ability to ask questions about the material akidah morals given. The implementation of the learning method start with a question in learning akidah akhlak at MA Mazro'atul Huda Wonorenggo Karanganyar Demak has been implemented properly. Second, the supporting factors of the method, namely: from the mediator or educators, the factors of the education participants, the advantages of the learning start with a question method itself and the infrastructure such as the learning media used. The third, the inhibiting factors, namely: very limited time and factors from students. Keywords: Methods, learning start with a question, learning akidah akhlak